Ad hoc public disclosure obligations of public companies on the capital market - Marjanski, Vladimir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
The author gives a comprehensive analysis of the obligations of public companies regarding the provision of periodical (ad hoc) information to the public on the capital market. Ad hoc disclosure is to achieve a number of aims. It is one of the devices to secure the market's functional abilities. By means of regularly fulfilling this obligation, the market is provided with all the relevant information necessary to form adequate prices of market materials - i.e. securities and other financial instruments (the function of market protection). Investors are thus being able to aptly respond to modified circumstances and deliver investment decisions whether to buy or sell market materials the price of which are being changed (the function of investor protection). Due to the fact that the duty of ad hoc disclosure encompasses the obligation to reveal insider information directly affecting the emitter, ad hoc disclosure serves as a preventive measure, i.e. as a protection against illicit trade with insider information (the function of prevention against the abuse of insider information).